Biofertilizers: An Emerging Trend in Agricultural Sustainability - Yapa, N.; Lakmali, D.; De Zoysa; Silva, K.S.; Manawadu, C.; Herath, B.M.; Madhushan, A.; Perera, G.; Ratnayakae, O.; Kapilan, R.; Rathnayake, A.; Sirisena, A.I.; et al. (Chiang Mai Journal of Science, 2022)
Although biofertilizers have been used for an exceptionally long time, challenges still remain in using them to phase out chemical fertilizers. Chemical fertilizers generate environmental pollution and negatively impact benefi cial organisms as well as human and animal wellbeing, causing a paradigm shift towards safer improved biofertilizers. Hence, improving the arsenal of microbial inoculants such as plant-growth-promoting rhizobacteria (PGPR) and plant growth-promoting fungi (PGPF), use of microbial consortia, use of uncommon inoculants such as extremophiles and microalgae, development of customized biofertilizers to suit the conditions of the fi elds and their geographical locations, identifying and popularizing other benefi cial aspects of biofertilizers to use them as tools for bioremediation, improved plant physiology and degradation of pesticides have become the trends of biofertilizers. However, soil application of biofertilizers has limited success yet and to be explored. Because of the interactions of soil- introduced PGPR and PGPF can be excluded by the more resilient microbiome in soil. Therefore, different strategies have to be employed to facilitate complex interactions with soil, environment and phytomicrobiomes. New molecular technologies allow for using metagenomics, metatranscriptomics, metaproteomics and metabolomics to spur development. Phytomicrobiome engineering is also used in synthetic biology also may offer new trend. These will be key in developing the next generation of biofertilizers.
Keywords: Microalgae; Microbial consortia; Mycorrhiza; Omics; PGPR; PGPF